1999
DOI: 10.1023/a:1006960407008
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 1. The biological effects of carnosine, a natural hydrophilic neuropeptide, on the reactive oxygen species (ROS) pathological generation are reviewed. 2. We describe direct antioxidant action observed in the in vitro experiments. 3. Carnosine was found to effect metabolism indirectly. These effects are reflected in ROS turnover regulation and lipid peroxidation (LPO) processes. 4. During brain ischemia carnosine acts as a neuroprotector, contributing to better cerebral blood flow restoration, electroencephalog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In this context, we have previously demonstrated for the first time to our knowledge that carnosine (and anserine) are present also in rat myocardium at significant levels (∼50 nmoles/g). This stems as another important finding at the light of the well documented carnosine's anti-ischemic activity, demonstrated in isolated rat heart and in vivo [20,21]. Future studies will be focused to demonstrate the suitability of this MS approach to detect/quantitate HD-HNE adduct formation in animal heart tissue under conditions that mimic pathological situations (myocardial post-ischemic conditions as a model of cardiovascular diseases), where HNE formation is massively involved.…”
Section: Discussionmentioning
confidence: 89%
“…In this context, we have previously demonstrated for the first time to our knowledge that carnosine (and anserine) are present also in rat myocardium at significant levels (∼50 nmoles/g). This stems as another important finding at the light of the well documented carnosine's anti-ischemic activity, demonstrated in isolated rat heart and in vivo [20,21]. Future studies will be focused to demonstrate the suitability of this MS approach to detect/quantitate HD-HNE adduct formation in animal heart tissue under conditions that mimic pathological situations (myocardial post-ischemic conditions as a model of cardiovascular diseases), where HNE formation is massively involved.…”
Section: Discussionmentioning
confidence: 89%
“…[35] Carnosine is also effective in the prevention and partial reversal of cataracts [36] and in the treatment of Wilsons disease [37] and Alzheimers due to its metal chelating and free radical scavenging ability and also acting as a β-amyloid toxicity inhibitor. [35,38] It has also been shown that carnosine acts as a neuroprotector [39,40] and can retard tumour growth in mouse models. [41] More recently it has been reported that carnosine can prevent cell proliferation in colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the year 2000 Biochemistry -Moscow dedicated an entire issue to the "Centenary of Gulewitsch's Discovery", reviewing most of the information available at that time about carnosine and its related natural analogs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. We will, in the present review, mainly focus on the design of carnosine synthetic analogs, their structure-activity relationship studies and the proposed mechanism of action for the carbonyl scavenging activity, after a brief introduction on carnosine and its physiological roles.…”
Section: Introductionmentioning
confidence: 99%